Evaluation of postoperative handover using a tool to assess information transfer and teamwork. - Nagpal, K; Abboudi, M; Fischler, L; Schmidt, T; Vats, A; Manchanda, C; Sevdalis, N; Scheidegger, D; Vincent, C; Moorthy, K (2011)
OBJECTIVE: To assess the feasibility, validity, and reliability of a postoperative Handover Assessment Tool (PoHAT) and to evaluate the current practices of the postoperative handover at 2 large European hospitals. BACKGROUND: Postoperative handover is one of the most critical phases in the care of a patient undergoing surgery. However, handovers are largely informal and variable. A thorough understanding of the problem is necessary before safety solutions can be considered. METHODS: Postoperative Handover Assessment Tool (PoHAT) was developed through task analysis, semistructured interviews, literature review, and learned society guidelines. Subsequent validation was done by the Delphi technique. Feasibility and reliability were then evaluated by direct observation of handovers at 2 large European hospitals. Outcomes measures included information omissions, task errors, teamwork evaluation, duration of handover, and number of distractions. RESULTS: The tool was feasible to use and inter-rater reliability was excellent (r = 0.96, P < 0.001). Evaluation of handover at the 2 study sites revealed a median of 8 information omissions per handover at both the centers (IQR 7-10). There were a median of 3 task errors per handover (IQR 2-4). Thirty-five percent of handovers had distractions, which included competing demands for nurse attention, bleeps, and case-irrelevant communication. CONCLUSION: This study has established the feasibility, validity, and reliability of a tool for evaluating postoperative handover. In addition to serving as an objective measure of postoperative handover, the tool can also be used to evaluate the efficacy of any intervention developed to improve this process. The study has also shown that postoperative handover is characterized by incomplete transfer of information and failures in the performance of key tasks.